Heavy metal accumulation and the expression of the copA and nikA genes in Bacillus subtilis AG4 isolated from the Sotk Gold Mine in Armenia - Margaryan, A. A.; H. H. Panosyan; N. K. Birkeland; A. H. Trchounian (ՀՀ ԳԱԱ հրատ.)
he growth response, heavy metal bioaccumulation ability and the expression of the copA, nikA and czcD genes in the presence of different concentrations of a combination of Cu(II), Ni(II), Zn(II) and Cd(II) metals of Bacillus subtilis AG4 isolated from the Sotk Gold Mine (Armenia) have been studied. Minimal inhibitory concentrations of Cu(II), Ni(II), Zn(II) and Cd(II) metals were 3.5 mM, 4.5 mM, 1 mM and 0.5 mM respectively. Ուսումնասիրվել է Սոթքի ոսկու հանքից (Հայաստան) մեկուսացված Bacillus subtilis AG4 շտամի աճը, մետաղները կենսակուտակելու ունակությունը, ինչպես նաև copA, nikA և czcD գեների էքսպրեսիան միջավայրում Cu(II), Ni(II), Zn(II) և Cd(II) տարբեր կոնցենտրացիաների համակցությունների պայմաններում: Изучены рост, биоаккумулирующая спосoбность, а также экспрессия генов copA, nikA и czcD штамма Bacillus subtilis AG4, изолированного из Сотского месторождения золота (Армения), при различных концентрациях комплекса металлов Cu(II), Ni(II), Zn(II) и Cd(II) в питательной среде. Минимальная ингибирующая концентрация металлов Cu(II), Ni(II), Zn(II) и Cd(II) составляла 3.5 мМ, 4.5 мМ, 1.0 мМ и 0.5 мМ, соответственно.
Keywords: Biology; Molecular Biology